Veterinarians are most popular source of information utilized by cow-calf producers - S.J. Breiner; S.A. Grau; B.B. Barnhardt; A.M. Bryant; Kris Boone; Dale A. Blasi; Ted C. Schroeder; Ryan M. Breiner (Kansas Agricultural Experiment Station Research Reports, 2007)
Sources and channels of information used among agriculturalists have long been important issues in Cooperative Extension. A source is an entity that originates a message. By understanding from whom producers receive messages, there exists a better framework to deliver information. Moreover, when considering the demographics of today's producers, as well as the sources of information utilized, the industry can work toward better educating and understanding the concerns of these individuals.
Keywords: Cattlemen' s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; Veterinarians; Cow-calf producers